Identification of Aryl Polyamines Derivatives as Anti-Trypanosoma cruzi Agents Targeting Iron Superoxide Dismutase - Rubén Martín-Escolano; Daniel Molina-Carreño; Javier Martín-Escolano; Mª Paz Clares; Cristina Galiana-Roselló; Jorge González-García; Nuria Cirauqui; José M. Llinares; María José Rosales; Enrique García-España; Clotilde Marín (MDPI AG, 2022)
Chagas disease (CD) is a tropical and potentially fatal infection caused by Trypanosoma cruzi. Although CD was limited to Latin America as a silent disease, CD has become widespread as a result of globalization. Currently, 6-8 million people are infected worldwide, and no effective treatment is available. Here, we identify new effective agents against T. cruzi. In short, 16 aryl polyamines were screened in vitro against different T. cruzi strains, and lead compounds were evaluated in vivo after oral administration in both the acute and chronic infections. The mode of action was also evaluated at the energetic level, and its high activity profile could be ascribed to a mitochondria-dependent bioenergetic collapse and redox stress by inhibition of the Fe-SOD enzyme. We present compound 15 as a potential compound that provides a step forward for the development of new agents to combat CD.